AcceleratorMass Spectrometry and Its Applications in Archaeology, Geology, and Environmental Research - Kretschmer, Wolfgang (Handbook of Particle Detection and Imaging, 2021)
Accelerator mass spectrometry (AMS) is an ultrasensitive method for the measurement of isotope ratios in the range of 10-12-10-15. Most frequently the 14C/12C ratio from biogenic samples is determined which gives information on the age of the sample of up to 50 ka with a precision of typically 40-80 years. In this chapter the radiocarbon method is discussed and various applications to interdisciplinary research are presented. One application at the Erlangen AMS facility is the 14C dating of sediment samples which together with simultaneous pollen analyses can establish a better chronology of climate and vegetation during Holocene in Germany. For an enhanced reliability of sediment dating different fractions like bulk sediments, pollen grains, macrofossils, and humic acids have been measured. For environmental research the 14C content of aldehydes from indoor air samples can be used to disentangle the anthropogenic or biogenic origin of these compounds. Finally interesting archaeological samples from a Persian mummy are discussed.
CRIS-Team Scopus Importer:2024-12-16